Enzymatic hydrolysis of sago fronds and leaves for production of sugar - Muhammad Norhelmi, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2014)
Production of sugar was performed in 1 L lab scale vessel from two types of sample (sago leaves and fronds). The samples were divided into three conditions (syrup, dried solid and fresh solid). The syrup was enzymatically hydrolyzed for 26 hours (2 hours for liquefaction and 24 hours for saccharification). The solid sample was hydrolyzed for 16 hours (direct mixing method) at different concentrations (i.e. 50g dried solid sample in IL water). The hydrolysate was purified by filtration using powdered activated charcoal (PAC) and the sugar concentration was measured based on dextrose equivalent (DE). The highest sugar recovery from solid was produced from fresh fronds solid (38.77%). The iodine test shows that the leaves and fronds syrup contain amylopectin starch. It was observed, both sago leaves and fronds produced glucose and cellobiose, with solve lactic acid in sago fronds. While waiting for the sago palm to be mature, the farmer can use the leaves and fronds for the production of sugar that can generate extra income. Therefore, enzymatic hydrolysis of sago leaves and fronds had a potential to be the alternative raw material for the production of sugar and reduce environmental pollution.